Framed spaces : photography and memory in contemporary installation art - McTighe, Monica E. (Interfaces, studies in visual culture., 2012)
"While earlier theorists held up "experience" as the defining character of installation art, few people have had the opportunity to walk through celebrated installation pieces from the past. Instead, installation art of the past is known through archival photographs that limit, define, and frame the experience of the viewer. Monica E. McTighe argues that the rise of photographic-based theories of perception and experience, coupled with the inherent closeness of installation art to the field of photography, had a profound impact on the very nature of installation art, leading to a flood of photography- and film-based installations. With its close readings of specific works, Framed Spaces will appeal to art historians and theorists across a broad spectrum of the visual arts"--Provided by publisher.